THE EFFECTS OF CLOCITY MEDIA ON SPEAKING SKILLS OF CHILDREN AGED 5-6 YEARS - Mallevi Agustin Ningrum; Septieniansyah Catur Yogiehastuti (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2019)
This study was motivated by the lack of speaking skills in children aged 5-6 years. In order to overcome these problems, in this study, clocity media was chosen to increase vocabularies when children tell stories related to time. This study used an experimental research design. The data analysis technique used was t-test. The pre-test results showed an average of 0.160, while the posttest results showed an average of 0.263. The results of the pretest and posttest show that it was greater than 0.05 so the data was normally distributed. The results showed a significant level of 0.000, meaning less than 0.05, so it can be concluded that there was a significant influence of the use of clocity media on the speaking skills of children aged 5-6 years.